Handbook for social work writing - Mason, Susan Elizabeth; Zeitlin, Wendy (New York, NY : Routledge, 2024)
"This concise, accessible, and engaging handbook offers a companion for social work students to acquire professional and competency-based writing skills"--
Introduction: getting the most out of this handbook for social work writing -- Writing for social work courses -- Writing for the field: write like a professional social worker -- Other forms of communication -- Using technology to make writing easier -- The basics of APA writing style -- Common writing challenges -- Skills in support of critical writing.
Keywords: Communication in social work; Social case work reporting; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General